Civil Society Elites: Exploring the Composition, Reproduction, Integration, and Contestation of Civil Society Actors at the Top - Johansson, Håkan; Meeuwisse, Anna (Palgrave Studies in Third Sector Research, 2024)
This open access book introduces a groundbreaking concept - civil society elites - and serves as an essential resource for scholars, researchers and students interested in the complexities of power and influence within contemporary civil societies. Through a series of unique empirical studies, the authors offer a comprehensive examination of the individuals occupying the upper echelons of influential civil society organisations and movements. By delving into the factors that propel individuals into key positions and examining the connections between civil society leaders within and across sectors, the book offers insight into the mechanisms that shape access to powerful positions in civil societies. As a reflection of current debates on elites and populism, the book furthermore explores the expression and conceptualisation of counter-elite positions and criticism of civil society elites. With its original approach, the book serves as a catalyst for further research into inequalities, power structures and elites within civil societies.